Plasmodium vivax Cell Traversal Protein for Ookinetes and Sporozoites (CelTOS) Functionally Restricted Regions Are Involved in Specific Host-Pathogen Interactions - Arévalo-Pinzón, Gabriela; Garzón-Ospina, Diego; Pulido, Fredy A.; Bermúdez, Maritza; Forero-Rodríguez, Johanna; Rodríguez-Mesa, Xandy M.; Reyes-Guarín, Leidy P.; Suárez, Carlos F.; Patarroyo, Manuel A. (Frontiers in Cellular and Infection Microbiology, 2020)
Following the injection of Plasmodium sporozoites by a female Anopheles mosquito into the dermis, they become engaged on a long journey to hepatic tissue where they must migrate through different types of cell to become established in parasitophorous vacuoles in hepatocytes. Studies have shown that proteins such as cell traversal protein for Plasmodium ookinetes and sporozoites (CelTOS) play a crucial role in cell-traversal ability. Although CelTOS has been extensively studied in various species and included in pre-clinical assays it remains unknown which P. vivax CelTOS (PvCelTOS) regions are key in its interaction with traversed or target cells (Kupffer or hepatocytes) and what type of pressure, association and polymorphism these important regions could have to improve their candidacy as important vaccine antigens. This work has described producing a recombinant PvCelTOS which was recognized by ~30% P. vivax-infected individuals, thereby confirming its ability for inducing a natural immune response. PvCelTOS' genetic diversity in Colombia and its ability to interact with HeLa (traversal cell) and/or HepG2 cell (target cell) external membrane have been assessed. One region in the PvCelTOS amino-terminal region and another in its C-terminus were seen to be participating in host-pathogen interactions. These regions had important functional constraint signals (ω < 0.3 and several sites under negative selection) and were able to inhibit specific rPvCelTOS binding to HeLa cells. This led to suggesting that sequences between aa 41–60 (40833) and 141–160 (40838) represent promising candidates for an anti-P. vivax subunit-based vaccine.